LOCAL GOVERNMENT ISSUES AFTER THE ENACTMENT OF LAW 11 OF 2020 ON JOB CREATION: MASALAH PEMERINTAHAN DAERAH PASCA DISAHKANNYA UNDANG-UNDANG 11 TAHUN 2020 TENTANG CIPTA KERJA - Baihaqi, Syahrial Arsyi (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2024)
With the enactment of Law Number 23 of 2014 concerning Regional Government, it provides new regulations regarding the division of authority between levels of government. There are several administrations of government affairs which were previously part of the authority of the Regency/City and later became the authority of the State. The administration of government consists of the implementation of mandatory government and the implementation of elective government which is divided between the central government, provincial regions and regency/municipal regions. Mandatory Government Affairs are divided into Mandatory Government Affairs relating to Basic Services and Mandatory Government Affairs which are not related to Basic Services. The relationship of authority between the Central Government and Regional Governments in the system of the Unitary State of the Republic of Indonesia gave rise to the concepts of centralization and decentralization. The implementation of Regional Autonomy after the existence of Law Number 11 of 2020 concerning Job Creation took over the authority of the regional government, the authority of the Regional Government carried out by the Central Government can affect the existing government system in the region. Adjusted to the administration of government in the implementation of regional autonomy, this can affect local revenue which can have a negative impact on the area.